Structural Studies of the Complexes of Lanthanides(III) with N-m-Methylbenzene Oxamic Acid - Kumar Sharma, Vinod (Asian Journal of Chemistry, 2010)
Potentiometric studies have been cited for the formation of 1 : 3 lanthanide N-m-methylbenzene oxamic acid (NMMBOA) complexes. The complexes are found insoluble in common organic solvents but soluble in hot mineral acids and strong alkali. They are sufficiently thermally stable upto 240ºC. The complexes have been characterised on the elemental analysis, thermal and infra red studies. The ligand behaves as a monobasic bidentate O–O donor.